Desarrollo de embutido de pasta fina a base de subproducto del camarón (Litopenaeus vannamei) incorporando Bactoferm LHP (Pediococcus acidilactici y Pediococcus pentosaceus). - Diaz Ruiz, Josthyn Paul (2025)
This research addresses the valorization of broken shrimp from the Ecuadorian shrimp industry, which represents 25,000 tons of by-products annually. A sausage is developed using Bactoferm LHP (Pediococcus acidilactici and Pediococcus pentosaceus) as a starter culture, following the NTE INEN 1388:96 standard. A bifactorial design evaluates four concentrations of the culture (0%, 0.2%, 0.3%, 0.5%) and two binders (potato and cassava starch at 3%), with fermentation at ≤15±2°C for 48 hours. The results show a decrease in pH (7.25-6.22), an increase in acidity (0.21%-0.84%), variations in moisture (71.32%-75.76%), ash content (2.42%-2.61%), and cooking loss (4.65%-13.26%). The water retention capacity does not show significant differences (7.88%-12.22%). The sensory evaluation indicates differences in color, texture, and acceptability, highlighting the treatment with 0.5% culture and potato starch. Microbiological analyses confirm the absence of pathogens, with the growth of lactic acid bacteria proportional to the concentration of the culture (R²=0.85). The predominant flavor is sweet in all treatments. Treatment 7 (0.5% Bactoferm LHP and 3% potato starch) shows the least cooking loss, adequate ash content, favorable bacterial count, and maximum sensory acceptability (4/5). The product meets the microbiological and ash parameters of the regulations, although it does not reach the required pH after 48 hours, needing more fermentation time for complete optimization.